The coexistence of acorns with different maturation patterns explains acorn production variability in cork oak. - Pons, Josep; Pausas, Juli G. (Oecologia, 2012)
In dry areas such as Mediterranean ecosystems, fluctuations in seed production are typically explained by resource (water) availability. However, acorn production in cork oak (Quercus suber) populations shows a very low relationship to weather. Because cork oak trees produce acorns with different maturation patterns (annual and biennial), we hypothesized that acorn production in coexisting individuals with a different dominant acorn maturation type should respond differently to climatic factors and that disaggregating the trees according to their acorn-maturation pattern should provide a more proximal relation to weather factors. We assessed acorn production variability in fragmented cork oak populations of the eastern Iberian Peninsula by counting the total number of acorns in 155 trees during an 8-year period. An initial assessment of acorn production variability in relation to weather parameters yielded very low explained variance (7%). However, after the trees were grouped according to their dominant acorn maturation pattern, weather parameters were found to account for 44% of the variability in acorn crops, with trees with annual acorns exhibiting mast fruiting in years with reduced spring frost and shorter summer droughts and trees with biennial acorns showing the opposite pattern. Thus, conditions that negatively affect annual production could be beneficial for biennial production (and vice versa). The results highlight the importance of the resource-matching hypothesis for explaining acorn production in Quercus suber and suggest that different seed maturation types within a population may allow the species to deal with highly variable weather conditions. They also emphasize the importance of understanding acorn maturation patterns for interpreting masting cycles.
The following values have no corresponding Zotero field: accession-num: 22246473
Keywords: biomass; Evergreen oaks; Fruit; Fruit: growth & development; Hypothesis; Masting; Mediterranean Region; Mediterranean woodlands; Quercus; Quercus suber; Quercus: growth & development; Weather

Litter production in a Quercus suber forest of Montseny (NE Spain) and its relationship to meteorological conditions - Caritat, Antònia; García-Berthou, Emili; Lapeña, Roger; Vilar, Lluís (Ann. For. Sci., 2006)
From 1996 to 2002 the monthly litterfall in a Quercus suber forest ecosystem of Montseny (NE Spain) was recorded and its relationship to meteorological variables was statistically analysed. The average annual production (477 g m-2 yr-1) was similar to those found in other Mediterranean evergreen forests with relatively high rainfall. The main components were the leaves (55% of the total biomass), followed by acorns (22%) and twigs (16%). Litter production was highest during May and June, when the majority of the old leaves fell. When the meteorological conditions were favourable, a second leaf fall collection was observed. Acorn production in 2001 was about nine times that of the previous years, indicating a mast year. In general, the different litterfall components were highly correlated in time except for the acorns. Interannual covariation was significant for leaves/twigs and leaves/catkins. Catkins were the most variable component with also strong seasonality, acorns were also very variable with low seasonality, while leaves were less variable and with the strongest seasonality. After accounting for seasonal covariation, there were significant effects of rainfall on twig litterfall and of temperature on leaf litterfall, the years with highest leaf litterfall being the hottest.
Keywords: coark oak; iberian peninsula; litterfall; Mediterranean climate; Weather

The use of climatic parameters and indices in vegetation distribution. A case study in the Spanish Sistema Central. - Gavilán, Rosario G. (International journal of biometeorology, 2005)
In this study, over 100 phytoclimatic indices and other climatic parameters were calculated using the climatic data from 260 meteorological stations in a Mediterranean territory located in the centre of the Iberian Peninsula. The nature of these indices was very different; some of them expressed general climatic features (e.g. continentality), while others were formulated for different Mediterranean territories and included particular limits of those indices that expressed differences in vegetation distribution. We wanted to know whether all of these indices were able to explain changes in vegetation on a spatial scale, and whether their boundaries worked similarly to the original territory. As they were so numerous, we investigated whether any of them were redundant. To relate vegetation to climate parameters we preferred to use its hierarchical nature, in discrete units (characterized by one or more dominant or co-dominant species), although it is known to vary continuously. These units give clearer results in this kind of phytoclimatic study. We have therefore used the main communities that represent natural potential vegetation. Multivariate and estimative analyses were used as statistical methods. The classification showed different levels of correlation among climatic parameters, but all of them were over 0.5. One hundred and eleven parameters were grouped into five larger groups: temperature (T), annual pluviothermic indices (PTY), summer pluviothermic indices (SPT), winter potential evapotranspiration (WPET) and thermal continentality indices (K). The remaining parameters showed low correlations with these five groups; some of them revealed obvious spatial changes in vegetation, such as summer hydric parameters that were zero in most vegetation types but not in high mountain vegetation. Others showed no clear results. For example, the Kerner index, an index of thermal continentality, showed lower values than expected for certain particular types of vegetation. Parameters relating to the water balance turned out to be very discriminative for separating vegetation types according to the season or the month when water begins to be scarce. Thus, water availability in soils is a limiting factor for the development of vegetation in spring or autumn as well as in summer. As expected, precipitation and temperature discriminated the altitudinal levels of vegetation. Finally, these index limits only worked in the territories where they were formulated, or in nearby areas.
The following values have no corresponding Zotero field: accession-num: 15997399
Keywords: climate; climatic indices; Mediterranean vegetation; multivariate analysis; phytoclimatology; Plants; Plants: classification; Principal component analysis; Seasons; Spain; Vegetation distribution; Weather